Nursing Supervision and Electronic Medical Record Documentation Quality among Practicing Nurses: A Cross-Sectional Study - Wahyuningsih, Luh Gde Nita Sri; Susanti, NLP Dina; Wulandari, Sarah Kartika (Journal of Applied Nursing and Health, 2026)
Background: Digital transformation in healthcare has promoted the use of Electronic Medical Records (EMR) as the standard for nursing documentation. Supervision is a key managerial strategy influencing its successful implementation among practicing nurses. However, empirical evidence on how supervision components affect the quality of electronic nursing documentation in low- and middle-income countries remains limited. Therefore, this study aims to analyze the strategic role of nursing supervision in strengthening EMR documentation. Methods: This analytical cross-sectional study examined the relationship between the role of supervision and the strengthening of electronic medical records. The sample included 352 practicing nurses selected through total sampling. Data were collected using a validated and reliable structured questionnaire (Cronbach’s alpha > 0.60). Analysis was conducted using Spearman’s rank correlation and binary logistic regression to assess the relationship and influence of supervision on documentation quality. Results: The results showed that the supervision variable (planning, coordination, control, monitoring, and feedback) was significantly related to electronic medical record documentation (p < 0.001), with feedback being the most dominant factor (Exp(B)=233.049; 95% CI: 15,606–3480.287). Conclusion: Nursing supervision plays a strategic role in strengthening the implementation of Electronic Medical Record documentation. From a managerial and policy perspective, these findings confirm that strengthening the supervision system, primarily through standardized and continuous feedback mechanisms, should be a priority for nursing leaders and hospital management.